Toka-chaff cutter cervical trauma in COVID-19 lockdown: case report - Munjal, Manish; Rishi, Porshia; Tuli, Nitika; Sidhu, Harjinder; Munjal, Shubham; Dhillon, Harnoor (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Fodder cutter (toka) of both manual and powered type is among the commonest tool being used by people for the preparation of fodder for their cattle. Agricultural traumatic injuries can lead to serious disability and mortality. Out of the agricultural machinery related accidents the maximum occur with the chaff-cutters i.e. toka machines. An intriguing cervical trauma due to entanglement in agricultural implement while chopping fodder in a young individual is being reported, as there is no reference in global literature. Slightest mistake can lead to serious injuries with disastrous outcome.